Regional Head Policy Implementation for Batik Artisan Economic Empowerment: Kepala Wilayah Pelaksanaan Kebijakan untuk Pemberdayaan Ekonomi Pengrajin Batik - Priya Sulaksana; Ahmad Ma’ruf; Endah Saptutyningsih (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The batik industry is a major creative economy subsector that supports cultural preservation and local economic development, yet it faces constraints related to policy limitations, technological innovation, and market expansion. Specific Background: This study examines the implementation outcomes of regional head policies for batik industry advancement as a strategy for empowering artisans in Sleman Regency. Knowledge Gap: Prior batik-related studies commonly rely on descriptive or regression approaches, providing limited insight into complex interdependence among variables linking policy, implementation, and empowerment. Aims: Using MICMAC (Matrice d’Impacts Croisés Multiplication Application à un Classement), this study identifies the variables shaping the implementation of regional head policies in the batik industry system. Results: MICMAC mapping shows the Regional Head Policy (KKD) as the main driving variable with the strongest direct and indirect relations, while product and process innovation, market access and promotion, and artisans’ welfare emerge as strongly dependent variables; empirically, clearer innovation-oriented directives, bureaucratic simplification, and human resource quality are central to interpreting the policy’s operational meaning. Novelty: The study contributes a MICMAC-based structural mapping of complex influence–dependence relations in regional head policy implementation for batik industry governance in Sleman. Implications: The findings support policy recommendations focused on aligning regulations with technological innovation, facilitating market access expansion, and sustaining artisans’ economic livelihoods within the creative economy ecosystem. Highlight: MICMAC positioning ranks KKD as the primary pushing variable in the system. Product–process innovation, market access–promotion, and artisan welfare appear as strongly dependent variables. Clear innovation-oriented directives, streamlined bureaucracy, and higher human resource quality characterize the implementation pathway identified in the analysis. Keywords: Regional Head Policy, MICMAC Analysis, Batik Industry, Economic Empowerment, Market Access